2022
DOI: 10.1021/acs.biochem.2c00449
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Evaluation of a Cross-Linked Oligonucleotide as the First Nanomolar Inhibitor of APOBEC3A

Abstract: Drug resistance is a major problem associated with anticancer chemo-and immunotherapies. Recent advances in the understanding of resistance mechanisms have revealed that enzymes of the APOBEC3 (A3) family contribute to the development of drug resistance in multiple cancers. A3 enzymes are polynucleotide cytidine deaminases that convert cytosine to uracil (C→U) in single-stranded DNA (ssDNA) and in this way protect humans against viruses and mobile retroelements. On the other hand, cancer cells use A3s, especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 70 publications
1
18
0
Order By: Relevance
“…Prior studies have shown that linear ssDNA substrates with 2-deoxyzebularine (dZ) and 5-fluoro-dZ (FdZ) in place of the target cytosine are weak inhibitors of A3A (and A3B) [30][31][32] . Additional work by our group and others has shown greater inhibition of A3A in vitro with pre-formed U-shaped, hairpin dZ and FdZ transition-state trapping oligonucleotides [33][34] . Here, we use X-ray crystallography to reveal the first high-resolution structures of wildtype A3A-inhibited complexes and demonstrate the underlying mechanism of inhibition.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Prior studies have shown that linear ssDNA substrates with 2-deoxyzebularine (dZ) and 5-fluoro-dZ (FdZ) in place of the target cytosine are weak inhibitors of A3A (and A3B) [30][31][32] . Additional work by our group and others has shown greater inhibition of A3A in vitro with pre-formed U-shaped, hairpin dZ and FdZ transition-state trapping oligonucleotides [33][34] . Here, we use X-ray crystallography to reveal the first high-resolution structures of wildtype A3A-inhibited complexes and demonstrate the underlying mechanism of inhibition.…”
Section: Introductionmentioning
confidence: 76%
“…The general strategy for the synthesis of dZ and FdZ and their incorporation into DNA oligomers has been described by us elsewhere 33 . 3-[(Dimethylaminomethylidene)amino]-3 H -1,2,4-dithiazole-3-thione (DDTT, Sulfurizing Reagent II from GlenResearch, USA) was used for sulfurization of oligos.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our work on APOBEC3A highlights another example that links the integrity of the genome to ribosome biogenesis. Currently, cytidine deaminase inhibitors are being developed [reviewed in ( 26 )], including against APOBEC3A ( 90, 91 ), with a focus on their application in cancer therapy ( 92 ). APOBEC3A’s newfound function in ribosome biogenesis emphasizes it as a top candidate cytidine deaminase target for cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%